Demon days [compact disc] (Virgin Records, 2005)
The world's biggest virtual band is back with their highly anticipated second album 'Demon Days.' Danger Mouse and Blur's Damon Albarn create the music behind the scenes. Features the single 'Feel Good Inc.'